Three Cases of Leber’s Hereditary Optic Neuropathy with Rapid Increase in Visual Acuity After Gene Therapy - Zhang, Yong; Yuan, Jia-jia; Liu, Hong-li; Tian, Zhen; Liu, Si-wei; Li, Bin (Current Gene Therapy, 2019)
Background: During the first few trials of gene therapy for Leber’s hereditary optic neuropathy performed by our group, the visual acuity of the patients increased gradually over several months, or even years. However, in the current round of gene therapy for Leber’s hereditary optic neuropathy, we noted that the visual acuity of three patients increased rapidly, within a few days after treatment. Case presentation: Three patients who were diagnosed with mitochondrial gene 11778 mutation (associated with a G-to-A transition at Mt-11778 in the ND4 subunit gene of complex I of mitochondrial DNA that changes an arginine to histidine at amino acid 340) by genetic diagnosis were followed up three times before gene therapy, which lasted for 1 year, without spontaneous improvement of vision. Visual acuity in one or both eyes of each of the three patients increased rapidly after the initial gene therapy treatment. Conclusion: We suspect that in some patients with Leber’s hereditary optic neuropathy, a portion of the retinal ganglion cells might remain in a “dormant” state for a certain period of time; these may be activated, within an optimal timeframe, during gene therapy for Leber’s hereditary optic neuropathy.
Keywords: Leber' s hereditary optic neuropathy